PROTOTYPE SISTEM INFORMASI BIMBINGAN DAN KONSELING MENGGUNAKAN FIGMA - Ranti Putri; Rika Widya; Yanti Yusman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Guidance and counseling services are one of the efforts that must be held in schools to facilitate the development of students both individually and in groups. Currently there are still a number of schools that still provide conventional guidance and counseling services, where counseling services are still carried out offline (face to face) in the school counseling room. With the implementation of such guidance services and the identicality of the counseling room with students who have problems, students who are called or come to the counseling room get a negative opinion from other students. Even though counseling services in schools do not only deal with students who have problems, but counseling services in schools can be a facility that can be used by students to carry out guidance (academic, talents, interests, potential) and counseling (activities carried out by counselors (counseling teachers) and students with the aim of providing solutions and helping solve problems faced by students). For this reason, it is necessary to utilize technology so that counseling services can be carried out digitally. This research focuses on making a prototype guidance and counseling information system. Prototypes are made using figma with the aim of getting user experience. User experience is needed so that when the guidance and counseling information system is built it can suit the needs of the school.